Diabetic Retinopathy and Atherosclerosis: is there a Link? - Phillip Ellis, Thomas; Hassan Choudhury, Ruhul; Kaul, Kirti; Chopra, Mohit; Maria Kohner, Eva; Mary Tarr, Joanna; Chibber, Rakesh (Current Diabetes Reviews, 2013)
Diabetic retinopathy (DR) is the leading cause of blindness amongst the working-age population, and diabetes accelerated cardiovascular disease (CVD) the commonest cause of death in diabetic patients. Although, there is evidence suggesting a close association between DR and CVD, particularly in patients with Type 2 diabetes, the pathophysiology underlying the link is unclear. Here we review common risk factors and pathogenic mechanisms linking DR and CVD, and aim to highlight the need for a more holistic view of the management of diabetes and its complications. The understanding of the link between the two complications could eventually lead to refined management strategies and improved patient outcomes in the expanding diabetes epidemic.
Keywords: Diabetic retinopathy